2017
DOI: 10.1007/s11999-016-4882-4
|View full text |Cite
|
Sign up to set email alerts
|

Poor Survivorship and Frequent Complications at a Median of 10 Years After Metal-on-Metal Hip Resurfacing Revision

Abstract: BackgroundHigh short-term failure rates have been reported for several metal-on-metal hip resurfacing (MoMHR) designs. Early observations suggested that MoMHRs revised to total hip arthroplasties (THAs) for pseudotumor had more major complications and inferior patient-reported outcomes compared with other revision indications. However, little is known about implant survivorship and patient-reported outcomes at more than 5 years after MoMHR revision.Questions/purposes(1) What are the implant survivorship, propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
(75 reference statements)
1
34
0
1
Order By: Relevance
“…Matharu et al [24] noticed that 6% of cases required re-revision in a series of 48 failed MoM-HRAs converted to CoC-THAs. This may partly be attributed to the DAA because it potentially improves dynamic hip stability and has the ability to decrease the risk of dislocation after conversion [6].…”
Section: Discussionmentioning
confidence: 99%
“…Matharu et al [24] noticed that 6% of cases required re-revision in a series of 48 failed MoM-HRAs converted to CoC-THAs. This may partly be attributed to the DAA because it potentially improves dynamic hip stability and has the ability to decrease the risk of dislocation after conversion [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported high rates of prosthetic loosening and revision in patients with metal-on-metal joint prostheses made of CoCrMo and Ti alloy. [20][21][22] Therefore, we focused on the osteolysis-inducing effects of CoCrMo and Ti particles.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, revising the femoral head size to 28 mm or 32 mm, and performing seven metal-on-polyethylene total hip replacements when the soft tissues are damaged by a pseudotumor, resulted in five recurrent dislocations with rerevisions. Removing a wellfixed acetabular component resulted in aseptic loosening and rerevisions in two hips [5]. When the authors changed their techniques, MoMHR revision improved to 76% survivorship, closer to their 82% survivorship for their total hip replacements [5].…”
mentioning
confidence: 95%
“…Removing a wellfixed acetabular component resulted in aseptic loosening and rerevisions in two hips [5]. When the authors changed their techniques, MoMHR revision improved to 76% survivorship, closer to their 82% survivorship for their total hip replacements [5].…”
mentioning
confidence: 95%
See 1 more Smart Citation